2015
DOI: 10.1186/s40623-015-0280-5
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic electron acceleration during HILDCAA events: are precursor CIR magnetic storms important?

Abstract: We present a comparative study of high-intensity long-duration continuous AE activity (HILDCAA) events, both isolated and those occurring in the "recovery phase" of geomagnetic storms induced by corotating interaction regions (CIRs). The aim of this study is to determine the difference, if any, in relativistic electron acceleration and magnetospheric energy deposition. All HILDCAA events in solar cycle 23 (from 1995 through 2008) are used in this study. Isolated HILDCAA events are characterized by enhanced flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 86 publications
3
32
0
Order By: Relevance
“…The chorus in turn accelerates the ~100 keV electrons to relativistic energies. Reviews of this idea can be found in Tsurutani et al (, ), Kasahara et al (), Miyoshi et al (), and Hajra, Tsurutani, Echer, Gonzalez, Santolik (), Hajra, Tsurutani, Echer, Gonzalez, Brum, et al ().…”
Section: Effects Of Interplanetary Turbulencementioning
confidence: 99%
“…The chorus in turn accelerates the ~100 keV electrons to relativistic energies. Reviews of this idea can be found in Tsurutani et al (, ), Kasahara et al (), Miyoshi et al (), and Hajra, Tsurutani, Echer, Gonzalez, Santolik (), Hajra, Tsurutani, Echer, Gonzalez, Brum, et al ().…”
Section: Effects Of Interplanetary Turbulencementioning
confidence: 99%
“…Due to the injection of ∼ 10-100 keV electrons during the HILDCAAs, these events can lead to the acceleration of relativistic (∼ MeV) electrons in the outer Van Allen radiation belt (Hajra et al, 2014b(Hajra et al, , 2015aTsurutani et al, 2016). The relativistic "killer" electrons can cause rapid degradation of semiconductors and satellite sensors in orbits in this region (Guarnieri, 2005;Hajra et al, 2014bHajra et al, , 2015a.…”
Section: Introductionmentioning
confidence: 99%
“…The relativistic "killer" electrons can cause rapid degradation of semiconductors and satellite sensors in orbits in this region (Guarnieri, 2005;Hajra et al, 2014bHajra et al, , 2015a.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that mentioned above, HILDCAA is associated with the enhancement of magnetospheric relativistic electrons. Hajra et al (2015) compared it to the isolated HILDCAA events. They assume that about 10-100 keV electrons are injected into the inner magnetosphere during the events, so the anisotropic electrons generate electromagnetic chorus plasma waves constantly, and the chorus waves continuously accelerate the electron to MeV energies (Paulikas and Blake, 1979;Baker et al, 1986;Summers et al, 1998;Meredith et al, 2003;Tsurutani et al, 2006bTsurutani et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%